Modifikasi Stamping Dies Panel Dashboard dengan Penambahan Base plate untuk Mengatasi Masalah Scrap Macet - Sanurya Putri Purbaningrum; Edwin Sahrial Solih; Desy Agustin; Rizki Kurniawan (Jurnal Serambi Engineering, 2024)
Maintenance department often has problems with process transfer dies. One of the problems currently being faced is scrap jams that disrupt the production process. The accumulation of scrap results in damage to the product being processed. Therefore, the process must be stopped for 15 minutes to clean the scrap. This research aims to overcome the problem of stuck scrap on LHD dash panel dies by modifying the dies. Identification of causes and effects using a fishbone diagram resulted in the fact that the cause of the scrap jam was the method factor, namely the scrap sutter angle which was too sloping at 80 so that the scrap did not run smoothly and caused buildup in the process area. Dies modification is carried out by adding components to the base plate so that the scrap cutter angle increases. The modification process begins with measuring the components to be modified, followed by creating component designs using CAD software, assembly simulation, docking, machining and assembly processes. After assembly, the scrap sutter angle is measured. There is a change in the scrap sutter angle from 80to 280. The change in the scrap sutter angle makes the scrap material flow smoothly so that no scrap accumulates. From the calculation results it was found that the benefit after improvement was 31,040,000 rupiah per year.